2020
DOI: 10.3390/agronomy10050676
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Beech Bark Extract in the Sage (Salvia Officinalis L.) Plant Growth and Volatile Oil Profile

Abstract: The use of bioactive compounds can act in growth stimulation and also influence the biosynthesis of the metabolites in plants. The aim of this paper is to assess the influence of the beech (Fagus sylvatica L.) bark crude extract (BBCE) on the growth and development of sage (Salvia officinalis L.) plants. Special attention was given to the analysis of volatile oil obtained from the sage treated plant. Thus, the biological activity of BBCE was assessed by determining the germination capacity, biomass accumulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…The obtained results show the rich effect of the beech bark extract on the germination process. The stimulatory effect of beech bark extract on sage germination and biomass production was observed previously [ 10 ]. The results suggest possible enzymatic changes induced by BBE1000, influencing the lavender seeds germination capacity [ 19 ].…”
Section: Discussionsupporting
confidence: 65%
See 4 more Smart Citations
“…The obtained results show the rich effect of the beech bark extract on the germination process. The stimulatory effect of beech bark extract on sage germination and biomass production was observed previously [ 10 ]. The results suggest possible enzymatic changes induced by BBE1000, influencing the lavender seeds germination capacity [ 19 ].…”
Section: Discussionsupporting
confidence: 65%
“…In our previous research, we have shown that bark extracts act as bioregulators in sage crops, influencing the production of secondary metabolites [ 10 ]. Plant polyphenols have been reported to act as stimulators in metabolic processes in plants, with positive effects on the final product quality.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations